Knowledge and Practices Regarding Episiotomy and Perineal Care among Primiparous Women - Madiha A. Muhammad (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: An episiotomy is a surgical incision through the perineum made to provide sufficient area forthe delivery of the infant. It is one of the most common medical procedures performed among prim porouswomen, and has an aim to avoid lacerations of the perineum and rectum. Nowadays, according to differentobstetric protocols, 10-90% of delivering woman will have episiotomy, depending on which part of theworld they are having delivery morbidity. This study aimed to assess the knowledge and practice regardingepisiotomy and perianal care among primiporous women, in Erbil city.Methods: A descriptive study was conducted at postpartum units of Maternity Teaching Hospital in Erbilcity, during 2020. A purposive sample of 200 prim porous women was recruited to study. Data collection wasperformed through using a questionnaire format for interviewing the participants. The data were analyzedusing descriptive and inferential statistical analysis.Results: the study findings revealed that the majority of the samples were within the age group 26-33 old,majority of prim porous women they don’t have adequate knowledge and practice regarding Episiotomyand Perennial Care and have inadequate knowledge and practice regarding Episiotomy and perennial CareConclusions: Majority of prim porous women had poor knowledge and practice regarding Episiotomyand perennial Care. The study recommended increasing effort at improving awareness and knowledge onepisiotomy among ANC clients by including it in the health talks given during ANC visits. Women areadequately informed and counseled before an episiotomy is given to them.